Siedlungsgenetische Untersuchungen in Fars.: Ein Beitrag zum Wüstungsproblem im Orient - Kortum, Gerhard (ERDKUNDE, 1975)
The development of settlement in the more densely settled central steppe and the nomadic areas of the south Iranian province of Fars has not been continuous between its prehistoric origins and the modern phase of expansion. In many areas, periods of flourishing settlement were interspersed by periods of decline and settlement retreat. This often took on cyclical character. The numerous settlement traces of different epochs, for example in the Marv dasht Plain north of Shiraz, show that a number of systems overlay each other before the development of the recent modern settlement structure. The main sources for reconstruction of settlement development, apart from genetic traces in the landscape, are archaeological maps, Persian topographies and the accounts of European travellers. In contrast to Central Europe, many rural areas in Fars and Iran have a high incidence of settlement desertion. The reasons include climatic anomalies, dependence on quanats and other delicate irrigation works, the phase-like development of nomadism and frequent political unrest.